Local cultural practices of the sasak community and their potential role in stunting prevention in Lombok - Mukminah Mukminah; Najah Sholehah; Pahrurrozi Pahrurrozi (AcTion: Aceh Nutrition Journal, 2026)
Stunting is a persistent public health concern in Indonesia. Although national efforts to reduce stunting have been widely implemented, the integration of local cultural practices into community-based prevention strategies has received limited attention. This study aimed to identify the local wisdom of the Sasak people that can provide sustainable solutions for stunting prevention. This study employed a descriptive qualitative design and an exploratory ethnographic approach. The study was conducted in two high-burden stunting districts, East Lombok and North Lombok, Indonesia, from August to December 2025. Ten participants, including mothers, community health volunteers, and Sasak traditional leaders, were purposively selected. Data were collected through in-depth interviews, observations, and document analysis. The data were analyzed using thematic analysis, which involved data reduction, categorization, and interpretation. Several forms of local wisdom related to maternal and child health were identified, including traditional postpartum care practices, the consumption of nutritious local foods, breastfeeding traditions extending up to 24 months, and culturally based food taboos. Sasak local wisdom plays an important role in preventing stunting. In particular, the consumption of nutritious local foods and traditional postpartum practices supports maternal and child health. Furthermore, breastfeeding practices up to 24 months, which are influenced by cultural and religious values, promote exclusive breastfeeding and sustained optimal infant feeding practices. In conclusion, the local wisdom of the Sasak ethnic community has the potential to serve as a sustainable approach to stunting prevention, as these practices are deeply embedded in the community’s cultural and social lives.